0\\\\t=log_{\sqrt3}x\; \; ,\; \; \; t^2+t-6=0\; ,\; \; t_1=-3\; ,\; t_2=2\; \; (teorema\; Vieta)\\\\log_{\sqrt3}x=-3\; \; \Rightarrow \; \; x=(\sqrt3)^{-3}=\frac{1}{3\sqrt3}=\frac{\sqrt3}{9}\\\\log_{\sqrt3}x=2\; \; \Rightarrow \; \; x=(\sqrt3)^2=3\\\\Otvet:\; \; x=\frac{1}{3\sqrt3}\; ,\; \; x=3\; ." alt="log^2_{\sqrt3}x+log_{\sqrt3}x-6=0\; \; ,\; \; \; ODZ:\; \; x>0\\\\t=log_{\sqrt3}x\; \; ,\; \; \; t^2+t-6=0\; ,\; \; t_1=-3\; ,\; t_2=2\; \; (teorema\; Vieta)\\\\log_{\sqrt3}x=-3\; \; \Rightarrow \; \; x=(\sqrt3)^{-3}=\frac{1}{3\sqrt3}=\frac{\sqrt3}{9}\\\\log_{\sqrt3}x=2\; \; \Rightarrow \; \; x=(\sqrt3)^2=3\\\\Otvet:\; \; x=\frac{1}{3\sqrt3}\; ,\; \; x=3\; ." align="absmiddle" class="latex-formula">